2009
DOI: 10.1016/j.freeradbiomed.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects retinal cells from light-and oxidant stress-induced cell death

Abstract: Age-related macular degeneration (AMD) is a complex disease that has potential involvement of inflammatory and oxidative stress-related pathways in its pathogenesis. In search of effective therapeutic agents, we tested curcumin, a naturally-occurring compound with known antiinflammatory and anti-oxidative properties, in rat model of light induced retinal degeneration (LIRD) and in retina derived cell lines. We hypothesized that any compound effective against LIRD, which involves significant oxidative stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(153 citation statements)
references
References 52 publications
(50 reference statements)
2
150
1
Order By: Relevance
“…Flash ERGs were recorded with the Diagnosys Espion E2 ERG System (Diagnosys, LLC; Lowell, MA) as described in previous publications ( 15,16 ). For the assessment of rod photoreceptor function (scotopic ERG), four strobe fl ash stimuli were presented at fl ash intensities of Ϫ 2.3, Ϫ 1.3, 0.7, and 2.7 log cd.s/m 2 .…”
Section: Electroretinographymentioning
confidence: 99%
See 3 more Smart Citations
“…Flash ERGs were recorded with the Diagnosys Espion E2 ERG System (Diagnosys, LLC; Lowell, MA) as described in previous publications ( 15,16 ). For the assessment of rod photoreceptor function (scotopic ERG), four strobe fl ash stimuli were presented at fl ash intensities of Ϫ 2.3, Ϫ 1.3, 0.7, and 2.7 log cd.s/m 2 .…”
Section: Electroretinographymentioning
confidence: 99%
“…After ERG recordings, rats were euthanized by carbon dioxide asphyxiation for light microscopic evaluation of retinal structure following previously published methods ( 15,16 ). In brief, eyes were harvested and marked with a tattoo dye at the 12 o'clock position on the limbus and fi xed.…”
Section: Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…colleagues first reported that sulforaphane could prevent RPE cell death caused by treatments with menadione, t-butyl hydroperoxide, 4-hydroxynonenal and peroxynitrite (Gao et al, 2001). Since then numerous other studies reported the protective effects of a wide range of structurally-different NRF2 inducers including isothiocyanates (sulforaphane) (Gao & Talalay, 2004), polyphenols (curcumin, resveratrol and flavonoids) (Alex et al, 2010;Johnson et al, 2009;Mandal et al, 2009), 1,2,dithiole-3-thiones (oltipraz) (Nelson et al, 2002), zinc (Ha et al, 2006) or triterpenoids (Pitha-Rowe et al, 2009). Many of them are naturally occurring compounds present in fruits and vegetables, making them ideal for dietary supplementation.…”
Section: Nrf2-dependent Antioxidant Defensementioning
confidence: 99%